Tannic acid modified iron-charcoal composite conductive carrier material as well as preparation method and application thereof
Through the low-temperature hydrothermal synthesis method of tanninic acid modified iron-biocarbon composite conductive carrier material, the problem of cumbersome and high cost of composite conductive materials in the prior art is solved, and the methane yield and electrons in the anaerobic system are significantly improved. Transfer efficiency achieves environmentally friendly and economical anaerobic wastewater treatment effect.
Patent Information
- Application Number
- CN202411504484.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-26
AI Technical Summary
The preparation process of composite conductive materials in existing anaerobic systems is cumbersome, costly, and potential biotoxicity and environmental risks, which limits their application in anaerobic wastewater treatment.
The tannin modified iron-biochar composite conductive carrier material is used to form a stable complex with tannin acid and iron and biochar through low-temperature hydrothermal synthesis method, which promotes electron transfer and reduces internal resistance and increases methane production.
It realizes low-cost and environmentally friendly preparation of composite conductive materials, significantly improves methane production and electron transfer efficiency in anaerobic systems, and solves the problems of conductive materials recycling and biotoxicity.
Smart Images

Figure CN119161018A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental restoration and pollution control, and specifically relates to a tannic acid modified iron-biochar composite conductive carrier material and a preparation method and application thereof. Background Art
[0002] Environmental pollution and energy shortages constrain the development of the global economy. Anaerobic wastewater treatment is a promising technology to address these two problems because it can recover energy (e.g., methane) from organic pollutants. However, the performance of methanogenesis in anaerobic systems is largely affected by complex interspecies interactions and low electron transfer rates between acidogens and methanogens. Therefore, enhancing electron transfer, promoting microbial metabolism, and improving anaerobic methanogenesis performance through a variety of regulatory strategies has become a research hotspot.
[0003] In recent years, more and more carbon-based and iron-based conductive materials (such as activated carbon, graphene, Fe3O4, ZVI) have been used to promote the direct interspecies electron transfer (DIET) process during anaerobic digestion. Carbon-based conductive materials have a large surface area and high stability and conductivity, providing a favorable environment for the growth of microorganisms. However, due to the small number of electron transfer sites on the surface of the material, the electron transfer between the cell surface and the carbon-based conductive material is limited, and the ability to directly use carbon-based conductive materials to improve the methane production of anaerobic systems is limited. Fe can serve as an active site for carbon-based conductive materials and enhance the conductivity of carbon-based conductive materials. Introducing iron into carbon-based conductive materials is expected to improve their electron transfer ability and promote the increase of methane production during anaerobic treatment.
[0004] However, composite conductive materials used in anaerobic systems usually require cumbersome preparation processes, high preparation costs and are difficult to recycle. The potential biological toxicity and environmental risks cannot be ignored, which greatly limits their engineering applications.
[0005] Therefore, how to provide a green synthesis method to prepare new composite conductive carrier materials is a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention
[0006] In view of this, the present invention discloses a tannic acid modified iron-biochar composite conductive carrier material and its preparation method and application. By using a green synthesis method to prepare a new composite conductive carrier, the problem of conductive material recycling in anaerobic systems is solved, methane production is increased, and microbial metabolism and direct interspecies electron transfer processes are accelerated.
[0007] It should be noted that tannic acid (TA), as a biodegradable natural plant polyphenol, has excellent metal chelation and electron transfer properties, and its own aromatic and quinone groups may also affect the anaerobic treatment process. Low-temperature heat treatment can maximize the retention of oxygen-containing functional groups in tannic acid-iron complexes, improve redox activity, and promote electron transfer. Iron and TA form stable complexes under neutral or alkaline conditions. In the preparation process, a conductive carrier carbon felt (CF) is introduced, and the conductive composite material is caused to grow in situ on the carrier through a pot of hydrothermal treatment, which has the advantages of promoting mass transfer, reducing internal resistance and enhancing microbial adhesion. At the same time, the green synthesis of plant polyphenols is more environmentally friendly and has lower cost. The strengthening effect on anaerobic wastewater treatment is also more durable and stable than a single carrier or iron / carbon material. Therefore, the present invention uses tannic acid low-temperature heat treatment to prepare a new green Fe-TA-C composite conductive carrier to strengthen direct interspecies electron transfer DIET in the anaerobic process, which is a promising strategy.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The first object of the present invention is to provide a method for preparing a tannic acid-modified iron-biochar composite conductive carrier material, the method specifically comprising the following steps:
[0010] (1) calcining the wood raw material at high temperature to obtain biochar, washing it with deionized water and ethanol alternately after natural cooling, drying it and sieving it for later use;
[0011] It should be noted that biochar prepared from waste raw materials is an environmentally friendly medium. Its rich porous structure provides more favorable conditions for the attachment of microorganisms and provides good active sites for electron transfer in anaerobic systems.
[0012] (2) dissolving the biochar obtained in step (1) and the soluble iron salt in deionized water and stirring magnetically for 30-40 minutes;
[0013] It should be noted that the conductivity of biochar can be improved by doping it with a small amount of iron.
[0014] (3) After the mixture is fully dissolved, tannic acid (TA) is added and stirring is continued for 6-8 hours, and the pH value of the resulting mixed solution is adjusted to 7-9 using NaOH or KOH;
[0015] It should be noted that tannic acid (TA) can be tightly bound to the carbon substrate through hydrogen bond interactions. Tannic acid and iron form stable complexes under neutral or alkaline conditions, promoting electron transfer between microorganisms and exogenous electron acceptors. Long-term stirring can promote the full reaction of tannic acid and iron.
[0016] (4) The mixed solution in step (3) and the pretreated carbon felt are transferred to a reactor for hydrothermal synthesis, and after natural cooling, the mixture is washed with deionized water and vacuum dried to obtain the tannic acid modified iron-biochar composite conductive carrier material.
[0017] It should be noted that the present invention forms a conductive composite carrier by hydrothermal synthesis of natively grown Fe-TA-C composite materials, which has the advantages of large surface area, strong conductivity and good chemical stability. On the one hand, it can be used as a fixed carrier without loss problems, avoiding the problem of powder material recovery and the impact on subsequent processes, and has certain economic feasibility. On the other hand, it can induce microbial attachment to form a functional biofilm, strengthen direct interspecies electron transfer DIET in the anaerobic process, and ultimately improve the methanogenic performance and achieve efficient energy recovery.
[0018] Optionally, in step (1), the biochar is wood biochar, the calcination temperature is 450-550°C, the calcination time is 1-3h, the heating rate is 5-10°C / min, it is washed alternately with deionized water and ethanol for 3-4 times, dried at 60-65°C, the drying time is 8-12h, and sieved to obtain 100-150 mesh powder for stand-alone use.
[0019] Optionally, in step (2), 0.50-1.0 g of biochar and 0.02-0.05 g of soluble iron salt are added to every 40-50 mL of deionized water; the soluble iron salt is preferably FeCl3·6H2O or Fe(NO3)3·6H2O.
[0020] Optionally, in step (3), 0.04-0.32 g of tannic acid is added, the molar ratio of tannic acid to iron is 1:1-1:3, and 0.1-0.2 M NaOH or KOH solution is added dropwise until the pH of the mixed solution is 7-9.
[0021] Optionally, in step (4), the carbon felt pretreatment method is: in a water bath at 80-90°C, place 2-5×2-5×0.1-0.2 cm 3 The carbon felt is soaked in a 30% hydrogen peroxide solution for 1-2 hours; rinsed with deionized water to a neutral pH value, and dried in an oven at 60-65°C for 3-6 hours to obtain a pretreated carbon felt. This allows the carbon felt to carry hydroxyl groups, increase the proportion of oxygen-containing functional groups, better combine with TA, enhance the redox ability of the composite conductive carrier material, and promote electron transfer.
[0022] Furthermore, in step (4), the hydrothermal temperature is 120-140°C, the hydrothermal synthesis time is 12-16h, and after natural cooling to below 60°C, it is washed with deionized water 3-4 times, the vacuum drying temperature is 60-65°C, and the drying time is 8-12h.
[0023] The second object of the present invention is to provide a tannic acid modified iron-biochar composite conductive carrier material prepared by the method as described above, wherein the conductive carrier material is a Fe-TA-C composite conductive carrier material that promotes electron transfer.
[0024] The third object of the present invention is to provide an application of a tannic acid modified iron-biochar composite conductive carrier material prepared by the method as described above in environmental remediation and pollution control technology.
[0025] Furthermore, the application of the tannic acid modified iron-biochar composite conductive carrier material in the anaerobic treatment of sewage and wastewater can be applied to various scenarios such as municipal sewage, industrial wastewater, aquaculture wastewater, etc.
[0026] Specifically, anaerobic sludge and tannic acid modified iron-biochar composite material / carrier are placed in an anaerobic reactor, and wastewater to be treated is introduced, mixed culture is carried out for 10-12 days, and organic pollutants are biodegraded, pH is maintained at 7.0-8.5, and hydraulic retention time is 12h. The concentration of anaerobic sludge is 5-6gVSS / L; the amount of composite material / carrier added is 0.05-0.1g / L; the anaerobic reactor includes intermittent flow, semi-continuous flow and continuous flow reactors; the operating temperature is 35-37℃, nitrogen blowing is 5-15min to achieve anaerobic environment in the reactor, and it is placed in a constant temperature magnetic stirrer with a stirring rate of 100-150r / min.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention prepares a tannic acid-modified iron-biochar composite conductive carrier by a simple low-temperature hydrothermal synthesis method, which has low raw material cost, simple method, good conductivity, recyclability and high stability.
[0029] (2) The novel conductive carrier of tannic acid-modified iron-biochar prepared by the present invention can store and release electrons, enhance the direct interspecies electron transfer between acidogenic bacteria and methanogenic bacteria during anaerobic treatment, and the carbon felt immobilization is conducive to the formation of biofilm, which not only solves the problem of conductive material recovery, but also significantly increases methane production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0031] Figure 1This is a flow chart for preparing the iron-biochar and tannic acid-modified iron-biochar composite conductive material / carrier in Example 1.
[0032] Figure 2 The scanning electron microscope images of the iron-biochar, tannic acid-modified iron-biochar composite conductive material (a) and the carrier (b) in Example 1 are shown.
[0033] Figure 3 The cyclic voltammetry curves (a) and electrochemical impedance spectroscopy (b) of the iron-biochar and tannic acid-modified iron-biochar composite conductive carrier materials in Example 2.
[0034] Figure 4 Schematic diagram of the structure of the anaerobic biological reaction processor in Examples 3 and 4.
[0035] Figure 5 The TOC concentration change (a) and the total biogas production (b) of the iron-biochar and tannic acid-modified iron-biochar composite conductive carrier materials in Example 3 measured at different reaction times during the enhanced anaerobic biological treatment of wastewater.
[0036] Figure 6 The TOC concentration change (a) and the total biogas production (b) of the iron-biochar and tannic acid-modified iron-biochar composite conductive carrier materials in Example 4 measured at different reaction times during the enhanced anaerobic biological treatment of wastewater. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0039] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0040] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0041] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0042] The invention discloses a tannic acid modified iron-biochar composite conductive carrier material and a preparation method and application thereof.
[0043] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0044] Example 1
[0045] A method for preparing a tannic acid-modified iron-biochar composite conductive carrier material comprises the following steps:
[0046] (1) calcining the wood raw material at high temperature to obtain biochar, washing it with deionized water and ethanol alternately after natural cooling, drying it and sieving it for later use;
[0047] (2) Dissolve biochar and FeCl3·6H2O in deionized water and stir magnetically for 30 min;
[0048] (3) After the mixture is fully dissolved, tannic acid (TA) is added and stirring is continued for 6 h. The pH value of the resulting mixed solution is adjusted to 7 using NaOH;
[0049] (4) The mixed solution in step (3) and the pretreated carbon felt were transferred to a 100 mL reactor for hydrothermal synthesis. After natural cooling, the mixture was washed with deionized water and vacuum dried to obtain a tannic acid-modified iron-biochar composite conductive carrier material named Fe-TA-C@CF.
[0050] In step (1), the biochar is wood biochar, the calcination temperature is 500° C., the calcination time is 2 h, it is washed alternately with deionized water and ethanol for 3 times, dried at 60° C., the drying time is 12 h, and sieved to obtain 150 mesh powder for stand-alone use.
[0051] In step (2), 1.0 g of biochar and 0.02 g of FeCl3·6H2O were added to every 40 mL of deionized water.
[0052] In step (3), 0.06 g of tannic acid is added, the molar ratio of tannic acid to iron is 1:2, and 0.1 M NaOH solution is added dropwise until the pH of the mixed solution is 7.
[0053] In step (4), the carbon felt pretreatment method is: in a 90°C water bath, 3 The carbon felt was immersed in a 30% hydrogen peroxide solution for 1.5 hours, rinsed with deionized water until the pH value was neutral, and dried in an oven at 60° C. for 5 hours to obtain the pretreated carbon felt.
[0054] In step (4), the hydrothermal temperature is 120° C., the hydrothermal synthesis time is 14 h, and after naturally cooling to below 60° C., the product is washed three times with deionized water. The vacuum drying temperature is 60° C., and the drying time is 12 h.
[0055] Among them, TA is not added in step (3), and the other steps are the same, to prepare an iron-biochar composite conductive carrier material, named Fe-C@CF; carbon felt is not added in step (4), and the other steps are the same, to prepare an iron-biochar composite material, named Fe-TA-C; TA is not added in step (3), carbon felt is not added in step (4), and the other steps are the same, to prepare a tannic acid-modified iron-biochar composite material, named Fe-C.
[0056] Preparation flow chart Figure 1 The scanning electron microscopy images of the composite material Fe-TA-C (a) and the carrier Fe-TA-C@CF (b) prepared by the above method are shown in FIG. Figure 2 shown.
[0057] Example 2
[0058] A method for preparing a tannic acid-modified iron-biochar composite conductive carrier material comprises the following steps:
[0059] (1) calcining the wood raw material at high temperature to obtain biochar, washing it with deionized water and ethanol alternately after natural cooling, drying it and sieving it for later use;
[0060] (2) Dissolve biochar and FeCl3·6H2O in deionized water and stir magnetically for 40 min;
[0061] (3) After the mixture is fully dissolved, tannic acid (TA) is added and stirring is continued for 8 h. The pH value of the resulting mixed solution is adjusted to 9 using NaOH;
[0062] (4) The mixed solution in step (3) and the pretreated carbon felt were transferred to a 100 mL reactor for hydrothermal synthesis. After natural cooling, the mixture was washed with deionized water and vacuum dried to obtain a tannic acid-modified iron-biochar composite conductive carrier material named Fe-TA-C@CF.
[0063] In step (1), the biochar is wood biochar, the calcination temperature is 550° C., the calcination time is 1.5 h, it is washed alternately with deionized water and ethanol for 3 times, dried at 60° C., the drying time is 12 h, and sieved to obtain 100 mesh powder for stand-alone use.
[0064] In step (2), 1.0 g of biochar and 0.05 g of FeCl3·6H2O were added to every 50 mL of deionized water.
[0065] In step (3), 0.31 g of tannic acid was added, the molar ratio of tannic acid to iron was 1:1, and 0.2 M NaOH solution was added dropwise until the pH of the mixed solution reached 9.
[0066] In step (4), the carbon felt pretreatment method is: in a water bath at 85°C, place a 4×4×0.1 cm 3 The carbon felt was immersed in a 30% hydrogen peroxide solution for 2 hours, rinsed with deionized water until the pH value was neutral, and dried in an oven at 60° C. for 6 hours to obtain the pretreated carbon felt.
[0067] In step (4), the hydrothermal temperature is 130° C., the hydrothermal synthesis time is 16 h, and after naturally cooling to below 60° C., the product is washed three times with deionized water, and the vacuum drying temperature is 65° C. and the product is dried for 8 h.
[0068] Wherein, TA was not added in step (3), and the other steps were the same, thereby preparing an iron-biochar composite conductive carrier material, which was named Fe-C@CF.
[0069] The composite conductive support materials Fe-C@CF and Fe-TA-C@CF prepared by the above method were subjected to electrochemical cyclic voltammetry curve CV (a) and electrochemical impedance spectroscopy EIS (b) tests. The data are shown in Figure 3 At a scan rate of 50 mV / s, the electrochemical active area (ECSA) of Fe-TA-C@CF was calculated by integrating the CV curve (a) and the electron transfer resistance (Rct) of Fe-TA-C@CF was calculated by equivalent circuit calculation of the EIS spectrum (b). <Fe-C@CF。
[0070] This shows that the interfacial mass transfer resistance can be significantly reduced due to the appropriate Fe-TA molar ratio doping; compared with Fe-C@CF, Fe-TA-C@CF has more active sites, stronger conductivity, and smaller electron transfer resistance, which can create a more suitable growth environment for anaerobic microorganisms and ultimately enhance direct interspecies electron transfer DIET.
[0071] Example 3
[0072] A method for preparing a tannic acid-modified iron-biochar composite conductive carrier material comprises the following steps:
[0073] (1) calcining the wood raw material at high temperature to obtain biochar, washing it with deionized water and ethanol alternately after natural cooling, drying it and sieving it for later use;
[0074] (2) Dissolve biochar and FeCl3·6H2O in deionized water and stir magnetically for 30 min;
[0075] (3) After the mixture is fully dissolved, tannic acid (TA) is added and stirring is continued for 6 h. The pH value of the resulting mixed solution is adjusted to 8 using NaOH;
[0076] (4) The mixed solution in step (3) and the pretreated carbon felt were transferred to a 100 mL reactor for hydrothermal synthesis. After natural cooling, the mixture was washed with deionized water and vacuum dried to obtain a tannic acid-modified iron-biochar composite conductive carrier material named Fe-TA-C@CF.
[0077] In step (1), the biochar is wood biochar, the calcination temperature is 450° C., the calcination time is 3 h, it is washed alternately with deionized water and ethanol for 4 times, dried at 65° C., the drying time is 8 h, and sieved to obtain 150 mesh powder for stand-alone use.
[0078] In step (2), 1.0 g of biochar and 0.02 g of FeCl3·6H2O were added to every 40 mL of deionized water.
[0079] In step (3), 0.04 g of tannic acid is added, the molar ratio of tannic acid to iron is 1:3, and 0.1 M NaOH solution is added dropwise until the pH of the mixed solution is 8.
[0080] In step (4), the carbon felt pretreatment method is: in a 90°C water bath, 3 The carbon felt was immersed in a 30% hydrogen peroxide solution for 1 hour, rinsed with deionized water until the pH value was neutral, and dried in an oven at 65°C for 3 hours to obtain the pretreated carbon felt.
[0081] In step (4), the hydrothermal temperature is 140° C., the hydrothermal synthesis time is 12 h, and after naturally cooling to below 60° C., the product is washed three times with deionized water, and the vacuum drying temperature is 65° C. and the product is dried for 8 h.
[0082] Among them, TA is not added in step (3), and the other steps are the same, to prepare an iron-biochar composite conductive carrier material, named Fe-C@CF; carbon felt is not added in step (4), and the other steps are the same, to prepare an iron-biochar composite material, named Fe-TA-C; TA is not added in step (3), carbon felt is not added in step (4), and the other steps are the same, to prepare a tannic acid-modified iron-biochar composite material, named Fe-C.
[0083] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following application examples are used to further illustrate the technical features disclosed in the present invention, but they should not be understood as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without creative work are also considered to fall within the scope of protection of the present invention.
[0084] Application Example 1
[0085] An application of a tannic acid modified iron-biochar composite conductive carrier material, specifically:
[0086] Anaerobic sludge and Fe-C / Fe-TA-C prepared by the method of Example 3 were placed in a 250mL anaerobic reaction bottle, 200mL simulated urban sewage was introduced, mixed culture was carried out for 10 days, and organic pollutants were biodegraded, the pH was maintained at 8.0, and the hydraulic retention time was 12h. Anaerobic sludge was taken from an anaerobic UASB reactor that had been operating stably in the laboratory for 1 year, the sludge concentration was 6gVSS / L, the Fe-C / Fe-TA-C addition amount was 0.05g / L, the liquid area at the bottom of the reaction bottle was the main reaction area, the upper part was the headspace gas, and the gas collection bag was connected to it for collecting the biogas produced by the reactor. The sampling port was submerged in the liquid surface with a hose bottom, and the upper part was sealed with a water stop clamp. Aeration with nitrogen for 10min to ensure an anaerobic environment. After the anaerobic reaction bottle was connected, it was placed in a constant temperature magnetic stirrer and cultured at 35°C, and the speed was maintained at 100r / min. The simulated urban sewage COD concentration was 500 mg COD / L (sodium acetate: glucose = 1:1), ammonium chloride and potassium dihydrogen phosphate provided the nitrogen source and phosphorus source required for microbial growth metabolism, respectively, where the mass ratio of carbon, nitrogen and phosphorus was 100:5:1, and the sodium bicarbonate concentration was 500 mg / L. 20 cycles were cycled, and water samples were taken at 4h, 8h, and 12h in the 1st, 3rd, 5th, 7th, 9th, 11th, 13th, 15th, 17th, and 19th cycles to determine the TOC in the solution, and the cumulative gas production and components were measured at the end of 20 cycles to evaluate the enhanced effect of Fe-C / Fe-TA-C conductive composite materials on anaerobic digestion treatment of urban sewage.
[0087] like Figure 5As shown in (a), the change of TOC over time was tested by a total organic carbon analyzer to explore the removal rate of organic matter. The control group was an anaerobic bioreactor without conductive materials and was named control. As can be seen from the figure, the TOC degradation rate was fast at first and then slowed down, and the TOC removal rate in the group with conductive materials was higher than that in the control group. Compared with the control group (75-80%), the TOC removal rate increased to 88-90% at a dosage of 0.05g / L Fe-C. When the same concentration of Fe-TA-C was added, the TOC removal rate was 95-97%, an increase of about 25%.
[0088] Figure 5 In (b), the cumulative gas production during the entire reaction process in the control group, Fe-C, and Fe-TA-C groups collected by air bags was detected by gas chromatography (TCD), and the main components were methane (CH4) and CO2. Compared with the control group, the cumulative methane production of the Fe-C and Fe-TA-C groups increased by 0.49 and 1.03 times, respectively, and the performance of Fe-TA-C was better than that of Fe-C. This shows that the simple low-temperature hydrothermal synthesis of tannic acid-modified iron-biochar composite conductive carrier material can be used as an excellent electron transfer carrier to promote direct interspecies electron transfer between hydrolytic acidifying bacteria and methanogens, thereby improving the removal rate of organic matter and methane production.
[0089] Application Example 2
[0090] An application of a tannic acid modified iron-biochar composite conductive carrier material, specifically:
[0091] Anaerobic sludge and Fe-C@CF / Fe-TA-C@CF prepared by the method of Example 4 were placed in a 250 mL anaerobic reaction bottle, and 200 mL of simulated urban sewage was introduced. Mixed culture was carried out for 10 days to biodegrade organic pollutants. The pH was maintained at 7.5 and the hydraulic retention time was 12 h. Anaerobic sludge was taken from an anaerobic UASB reactor that had been operating stably in the laboratory for 1 year. The sludge concentration was 5 gVSS / L. A Fe-C@CF / Fe-TA-C@CF carrier with an effective contact area of 2×2×0.1 cm 3, the loading amount is 0.01g, which is equivalent to the dosage of 0.05g / L. The liquid area at the bottom of the reaction bottle is the main reaction area, and the upper part is the headspace gas. The gas collection bag is connected to it to collect the biogas produced by the reactor. The carrier is fixed and suspended and immersed in the reaction bottle. The bottom of the sampling port is submerged above the liquid surface with a hose, and the upper part is sealed with a water stop clamp. Aeration with nitrogen for 15min to ensure an anaerobic environment. After the anaerobic reaction bottle is connected, it is placed in a constant temperature magnetic stirrer and cultured at 37℃, and the speed is maintained at 150r / min. The simulated urban sewage COD concentration is 500mg COD / L (sodium acetate: glucose = 1:1), ammonium chloride and potassium dihydrogen phosphate provide the nitrogen source and phosphorus source required for microbial growth metabolism, respectively, among which the mass ratio of carbon, nitrogen and phosphorus is 100:5:1, and the concentration of sodium bicarbonate is 500mg / L as a pH buffer. The cycle was repeated for 20 cycles. Water samples were taken at 4h, 8h, and 12h in the 1st, 3rd, 5th, 7th, 9th, 11th, 13th, 15th, 17th, and 19th cycles to determine the TOC in the solution. The cumulative gas production and components were determined at the end of the 20th cycle to evaluate the effect of Fe-C@CF / Fe-TA-C@CF composite conductive carrier material on anaerobic biological treatment of urban sewage through synergistic regulation of microorganism-carrier interface.
[0092] like Figure 6 As shown in (a), the change of TOC over time was tested by a total organic carbon analyzer to explore the removal rate of organic matter. The control group was an anaerobic bioreactor without the addition of a conductive carrier and was named control. As can be seen from the figure, the TOC degradation rate was fast at first and then slowed down, and the TOC removal rate in the group with the addition of a conductive carrier was higher than that in the control group. Compared with the control group (75-80%), the TOC removal rates of the reactors introducing Fe-C@CF and Fe-TA-C@CF were 90-92% and 94-95%, respectively.
[0093] Figure 6 In (b), the cumulative gas production during the entire reaction process in the control, Fe-C@CF, and Fe-TA-C@CF groups collected by air bags was detected by gas chromatography (TCD). Compared with the control group, the cumulative methane production of the Fe-C and Fe-TA-C groups increased by 1.76 and 1.85 times, respectively. This shows that the tannic acid-modified iron-biochar composite conductive carrier material can store and release electrons, induce the formation of functional biofilms, enhance the electron transfer at the microorganism-carrier interface, significantly increase methane production, solve the problem of conductive material recycling, and has low raw material cost and high stability. It has technical, environmental and economic advantages and is expected to become a sustainable alternative to traditional carriers in anaerobic wastewater biological treatment systems.
[0094] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a tannic acid-modified iron-biochar composite conductive carrier material, characterized in that: The method specifically comprises the following steps: (1) calcining the wood raw material at high temperature to obtain biochar, washing it with deionized water and ethanol alternately after natural cooling, drying it and sieving it for later use; (2) dissolving the biochar and soluble iron salt obtained in step (1) in deionized water and stirring magnetically; (3) adding tannic acid (TA) after the mixture is fully dissolved, and adjusting the pH value of the resulting mixed solution with alkali solution; (4) The mixed solution in step (3) and the pretreated carbon felt are transferred to a reactor for hydrothermal synthesis, and after natural cooling, the mixture is washed with deionized water and vacuum dried to obtain the tannic acid modified iron-biochar composite conductive carrier material.
2. The method for preparing the tannic acid modified iron-biochar composite conductive carrier material according to claim 1, characterized in that: In step (1), the biochar is wood biochar; the calcination temperature is 450-550°C, the calcination time is 1-3h, and the heating rate is 5-10°C / min; the biochar is washed alternately with deionized water and ethanol for 3-4 times, dried at 60-65°C for 8-12h, and sieved to obtain a 100-150 mesh powder for standby use.
3. The method for preparing the tannic acid modified iron-biochar composite conductive carrier material according to claim 1, characterized in that: In step (2), 0.50-1.0 g of biochar and 0.02-0.05 g of soluble iron salt are added to every 40-50 mL of deionized water.
4. The method for preparing the tannic acid modified iron-biochar composite conductive carrier material according to claim 1, characterized in that: In step (3), 0.04-0.32 g of tannic acid is added, the molar ratio of tannic acid to iron is 1:1-1:3, and 0.1-0.2 M NaOH or KOH solution is added dropwise until the pH of the mixed solution is 7-9.
5. The method for preparing the tannic acid modified iron-biochar composite conductive carrier material according to claim 1, characterized in that: In step (4), the carbon felt pretreatment method is: in a water bath at 80-90°C, place 2-5×2-5×0.1-0.2 cm 3 The carbon felt is immersed in a 30% hydrogen peroxide solution for 1-2 hours; it is rinsed with deionized water to a neutral pH value, and dried in an oven at 60-65° C. for 3-6 hours to obtain a pretreated carbon felt.
6. The method for preparing the tannic acid modified iron-biochar composite conductive carrier material according to claim 1 or 5, characterized in that: In step (4), the hydrothermal temperature is 120-140° C., the hydrothermal synthesis time is 12-16 h, and after naturally cooling to below 60° C., the product is washed with deionized water 3-4 times, the vacuum drying temperature is 60-65° C., and the drying time is 8-12 h.
7. A tannic acid modified iron-biochar composite conductive carrier material prepared by the method of claim 1, characterized in that: The conductive support material is a Fe-TA-C composite conductive support material that promotes electron transfer.
8. Application of the tannic acid modified iron-biochar composite conductive carrier material prepared by the method as claimed in claim 1 in environmental remediation and pollution control technology.
9. The use according to claim 8, characterized in that: The application of the tannic acid modified iron-biochar composite conductive carrier material in anaerobic treatment of sewage and wastewater.
Citation Information
Patent Citations
Embedded modified conductive bacteria for microbial fuel cell and preparation method of embedded modified conductive bacteria
CN111549021A
Iron-carbon composite carrier and application thereof
CN114455699A
Functional material for concentration and recovery of organic carbon in sewage and lateral flow anaerobic fermentation acid production as well as preparation method and application of functional material
CN118561365A
One-step method for preparing magnetic magnesium-iron layered double hydroxide (LDH)-biochar composite material and use thereof
US20230372892A1
Cited By
Coastal wetland nitrogen reduction, carbon sequestration and emission reduction method based on iron circulation
CN121405263A
